The challenges of SMEs to internationalization / Raja Alif Syahir Raja Abdul Hamid - Raja Abdul Hamid, Raja Alif Syahir (2014)
This research was conducted for the purpose of “to study the Challenges of SMEs to Internationalization”. The main objective of this research was to determine the relationship of Research & Development (R&D), Intellectual Property, Branding and Global Sourcing towards Challenges of SMEs to Internationalization It is part of researcher’s intention to provide a few suggestions for SMEs on how the challenges would impact them to go internationalization. This research paper is supported by primary and secondary data. As for the primary data, the researcher used questionnaire as a medium to collect information from small medium enterprise (SMEs) in Johor. On the other hand, reliable sources have been used by the researcher as primary data is obtained first hand by the researcher on the variables of interest for the specific purpose of the study. While for secondary data, the researcher use journal and electronic resources to make as references. The population for this study is 4877 SMEs companies and registered under SMEs Corp. The aim is to get 120 respondents, so 150 questionnaires were distributed. From 150 questionnaires that have been distributed, only 120 questionnaires managed to be collected. The researcher used Statistical Package for Social Science (SPSS) as a platform to analyzed data gained from the respondents. This research will provide the proof of whether all the independent variables have significant relationship towards challenges of SMEs to go internationalization. In order to achieve the objective, the researcher use Multiple Regression to calculate the relationship. From the findings, three variables have significant results while only one are not significant towards dependent variable. Recommendations for SMEs and future researcher also are provided in this study to use as guidance.